Measures of participation outcomes related to hand use for 2‐ to 12‐year‐old children with disabilities: a systematic review. Issue 4 (5th March 2013) - Chien, C‐W.; Rodger, S.; Copley, J.; McLaren, C.
Abstract Many interventions have been used to improve children's hand‐related impairments or hand skill performance in functional activities so as to promote life participation. There is thus a need to have suitable instruments assessing children's participation in life situations that specifically require hand use in order to support and evaluate such interventions. This systematic review investigated the availability of potential instruments that can be used to assess children's participation specifically in life situations requiring hand use. Clinical utility and evidence for psychometric properties were also sourced. Database searches initially identified measures that were used to evaluate participation of children aged 2–12 years, involved self‐ or proxy report or interview administration and had generic application for a range of disabilities/diagnoses. These measures were further evaluated to determine if they fulfilled the above inclusion criteria and contained at least 60% of the items involving hand use. Further searches for psychometric evidence were undertaken for the eligible measures. Fourteen measures were identified and nine met the inclusion criteria. However, none of these measures, except for the Children Helping Out: Responsibilities, Expectations, and Supports (CHORES), contained all items related to hand use. Most of the included measures had limited psychometric properties. Only the Children's Assessment of Participation and Enjoyment/Preferences for Activities of Children (CAPE/PAC), the School Function Assessment‐Participation section (SFA‐P) and the Children Participation Questionnaire (CPQ) revealed sufficient evidence of validity and reliability. The findings suggest a need for adapting existing participation measures or developing new ones that specifically assess participation in life situations requiring hand use to support interventions.